1933 Iowa Acts 47–48, ch. 30, § 24 - (:unkn) unknown (General Publisher, 1933)
Prohibited the use of a swivel gun or any other firearm, except those commonly shot from the shoulder or hand in hunting of game. Guns larger than a 10 gauge prohibited.
--
Keywords: HUNTING REGULATION